Tinjauan Maqashid Syariah terhadap Pemenuhan Hak Hadhonah Anak Pasca Perceraian pada Keluarga Gen Z di Kecamatan Bogor Barat, Kota Bogor - Arkam Arkian Liburaya (Lembaga Yasin AlSys, 2026)
Although children’s hadhanah rights following divorce have been widely examined from the perspective of Islamic family law, studies specifically analyzing their fulfillment in Generation Z families through Legal Protection Theory and Maqāṣid asy-Syarī‘ah remain limited. This study aimed to analyze the practice of fulfilling children’s hadhanah rights in Generation Z families following divorce, the factors influencing their fulfillment, and their conformity with the objectives of Maqāṣid asy-Syarī‘ah. The study employed a qualitative approach with a case study design and involved four informants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation and were subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing and verification. The findings showed that formal hadhanah rights rested with the mother, but daily caregiving was predominantly undertaken by the grandparents because economic demands required the mother to work. The father’s involvement in caregiving and the provision of child maintenance remained low, while economic conditions, parental emotional unpreparedness, and digital device use were factors influencing the implementation of hadhanah. From the perspective of Maqāṣid asy-Syarī‘ah, the fulfillment of hadhanah rights partially realized welfare, particularly in the preservation of religion (hifẓ al-dīn) and the fulfillment of the child’s physical needs (hifẓ al-nafs), but was not yet optimal in ensuring the child’s psychological protection and intellectual development (hifẓ al-‘aql). These findings contribute to the development of Philipus M. Hadjon’s Legal Protection Theory by integrating the principle of the best interest of the child and Maqāṣid asy-Syarī‘ah in assessing the effectiveness of fulfilling hadhanah rights following divorce. This study affirms the importance of strengthening the responsibilities of both parents and the effectiveness of legal protection to ensure the substantive fulfillment of children’s rights.